Acute Pancreatitis Complicated by Jejunal Hematoma in a Patient on Anti-Coagulants and Anti-Platelets - Chong, Vui Heng; Basir, Norwani; Yaakub, Aziman Bin (JOP. Journal of the Pancreas, 2010)
Context Pancreatitis can be associated with significant complications. Bowel hematoma is a rare complication and the second part of the duodenum is the most commonly affected site. Hematomas affecting other parts of the bowel are extremely rare. Case report A 53-year-old female with a history of atrial fibrillation and ischemic heart disease on anticoagulants and aspirin presented with abdominal pain of a few days duration which had worsened prior to presentation. This was associated with abdominal distension, vomiting and melena. Laboratory investigations showed elevated serum amylase, coagulopathy and severe anemia. Computed tomography imaging showed a jejunal hematoma and pancreatitis with peripancreatic inflammation. She responded to conservative treatment in addition to correction of the coagulopathy and a blood transfusion. Her symptoms were resolved within a few days and a repeat computed tomography scan two months later showed complete resolution of the hematoma and the pancreatitis. Conclusion Our case demonstrates a rare complication of acute pancreatitis in a patient with risk factors. Image: Jejunal hematoma and an irregular slightly swollen pancreatic body with peripancreatic fat streaking.